Study of phytoremediation by use of willow and rape - Máthé-Gáspár, Gabriella; Anton, Attila (Acta Biologica Szegediensis, 2005)
The mining activity surrounding the historic Pb/Zn mine at Gyöngyösoroszi (Hungary) causes heavy metal problems, being a potential risk for all organisms. One of the promising methods for cleaning of metal polluted soils is phytoremediation. Uptake and translocation of heavy metals by two selected plants, willow (Salix spp.) and rape (Brassica napus L.) was studied at Gyöngyösoroszi (Hungary), near to a lead/zinc mine, lower flooded area of Toka valley, where the soil is charged with high content of Pb, Zn, Cd, Cu (>1000, >3000, >18 and >280 mg/kg, respectively). The increased uptake and translocation rate of Cd and Zn from root to shoot indicated that phytoextraction technology is possible, while high Cu and Pb concentrations in roots with low translocation rate suggested the phytostabilisation method. Uptake and translocation rate of metals were generally higher in willow than in rape. Based on our results, under the present ecological conditions willow is rather applicable for phytoremediation purposes.